ประสิทธิภาพการใช้พลังงานของเครื่องปรับอากาศร่วมกับแผงรังผึ้งสำหรับ ลดอุณหภูมิอากาศเข้าแผงคอนเดนเซอร์ Efficiency of the Energy using of Air Condition and Cooling Pad for Reducing of inlet Air Temperature of Condenser - มั่นกลาง, เดชาวัต; ทรัพย์ปรุง, ภานุวัฒน์; ยาวะระ, สุดารัตน์; ยางคำ, ปิยะวรรณ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาและทดลองการทำงานของแผงรังผึ้งและเครื่องปรับอากาศ ผลวิจัย กรณีไม่เปิดนํ้าผ่านแผงรังผึ้งอุณหภูมิอากาศเข้าและออกจากแผงรังผึ้งเท่ากับ 34.76 ± 0.38 และ 32.82 ± 1.01 องศาเซลเซียส ความเร็วลมเท่ากับ 1.39 ± 0.01 และ 1.75 ± 0.08 เมตร/วินาที และ ความชื้นเท่ากับ 40.00 ± 0.07 และ 41.80 ± 0.83 เปอร์เซ็นต์ และกรณีเปิดนํ้าผ่านแผงรังผึ้งอุณหภูมิ อากาศเข้าและออกจากแผงรังผึ้งเท่ากับ 36.26 ± 0.38 และ 34.30 ± 0.23 องศาเซลเซียส ความเร็วลมเท่ากับ 0.90 ± 0.05 และ 0.92 ± 0.01 เมตร/วินาที และความชื้นเท่ากับ 56.80 ± 1.10 และ 58.40 ± 0.55 เปอร์เซ็นต์ อุณหภูมิผิวท่อขณะไม่เปิดนํ้าและเปิดนํ้าผ่านแผงรังผึ้งบริเวณทางออก คอมเพรสเซอร์เท่ากับ 87.5 และ 73.75 องศาเซลเซียส และบริเวณก่อนเข้าคอนเดนเซอร์เท่ากับ 74.10 และ 66.58 องศาเซลเซียส และเพื่อทดสอบประสิทธิภาพและประเมินความคุ้มค่าทางเศรษฐศาสตร์ของ ระบบ Cooling Pad เพื่อลดอุณหภูมิอากาศเข้าแผงคอนเดนเซอร์ของเครื่องปรับอากาศพบว่า ประสิทธิภาพในการทำงานของเครื่องปรับอากาศเท่ากับ 94.66 เปอร์เซ็นต์ สมรรถนะทางความเย็น ขณะเปิดเครื่องปรับอากาศแต่ไม่เปิดนํ้าผ่านแผงรังผึ้งและเปิดนํ้าผ่านแผงรังผึ้งเท่ากับ 6.58 และ 11.38 ประสิทธิภาพพลังงานขณะเปิดเครื่องปรับอากาศแต่ไม่เปิดนํ้าและเปิดนํ้าผ่านแผงรังผึ้งเท่ากับ 3.41 และ 11.14 บีทียู/ชั่วโมง/วัตต์ การถ่ายเทความร้อนโดยการพาแบบบังคับขณะไม่เปิดนํ้าและเปิดนํ้าผ่านแผงรังผึ้ง เท่ากับ 6.35 และ 9.51 วัตต์ ค่าเพาเวอร์แฟคเตอร์มิเตอร์เท่ากับ 9.16 ความคุ้มค่าทางเศรษฐศาสตร์พบว่าการติดตั้งระบบ Cooling Pad มีปริมาณพลังงานขณะเปิดเครื่องปรับอากาศให้ทำงาน แต่ไม่เปิดนํ้าผ่านแผงรังผึ้งเท่ากับ 76.56 หน่วยต่อวัน และเปิดนํ้าผ่านแผงรังผึ้งให้ทำงานร่วมกันเท่ากับ 64 หน่วยต่อวัน ปริมาณพลังงานลดลง 16.41 เปอร์เซ็นต์ ค่าไฟฟ้าขณะเปิดเครื่องปรับอากาศแต่ไม่เปิดนํ้าผ่านแผงรังผึ้งเท่ากับ 200.09 บาทต่อวัน และเปิดนํ้าผ่านแผงรังผึ้งเท่ากับ 167.27 บาทต่อวัน ค่าไฟฟ้าลดลง 16.40 เปอร์เซ็นต์ Abstract The objectives of this research were to study and test the operation of cooling pad and air condition system. The results found that elevated ear before Cooling Pad panels and Cooling Pad panels were not open water through the panels were 34.76 ± 0.38 and 32.82 ± 1.01oC. The wind speed were 1.39 ± 0.01 and 1.75 ± 0.08 m/s and moisture were 40.00 ± 0.07 and 41.80 ± 0.83 percent. Temperature before Cooling Pad panels and Cooling Pad panels when opening water through the panels were 36.26 ± 0.38 and 34.30 ± 0.23oC. Wind speed were 0.90 ± 0.05 and 0.92 ± 0.01 m/s and the humidity were 56.80 ± 1.10 and 58.40 ± 0.55 percent. Pipe surface temperatures, while opening water and opening water through the exit panels Cooling Pad were 87.5 and 73.75oC, The area before the condenser were 74.1 and 66.58oC. To test the performance and assess the economic worth of Cooling Pad to reduce the air temperature of the air conditioning condenser panel, we found that the performance of the air conditioner was 94.66 percent. Performance of the evening as the air conditioning, but not opening water through the honeycomb panels and opening water through Cooling Pad panels were equal to 6.58 and 11.38, energy efficiency, while the air conditioner, but not turning on the water and opening water through honeycomb panels were 3.41 and 11.14 BTU/h/W, respectively. Heat transfer by convection and forced opening water and open water through Cooling Pad panels were 6.35 and 9.51 W, with the power factor meter were equal to 9.16 the value of economics. In addition we found that the installation of Cooling Pad amount of energy as the air conditioning works, but not opening water through Cooling Pad panels were 75.56 units/day, and opening water through Cooling Pad panels, working together were 64 Units/day, energy intake decreased by 16.41 percent of the fire as the air conditioning. However, opening water through the Cooling Pad panel were 200.09 Baht/day and opening water through the Cooling Pad panel were 167.27 Baht/day for electricity decreased by 16.40 percent.